Investigation of Mortality Events Reveals Coinfections and Identification of Infectious Spleen and Kidney Necrosis Virus in Red Hybrid Tilapia in Thailand - Benya Chatkaewchai; Jidapa Yamkasem; Piyaporn Eiamcharoen; Methanan Kamklang; Pattrawut Saengnual; Orawan Boodde; Visanu Boonyawiwat; Win Surachetpong; Theeraporn Pulpipat (Journal of Fish Diseases, 2026)
Infectious diseases have become a major challenge in global tilapia aquaculture. This study investigated disease outbreaks affecting red hybrid tilapia ( Oreochromis spp.) by collecting 80 pooled samples from 36 farms between 2022 and 2024. Although the majority of samples tested positive for tilapia lake virus (TiLV), infectious spleen and kidney necrosis virus (ISKNV) was detected in 10% of the cases, specifically in fry and fingerlings originating from river‐based cage systems. All the ISKNV‐positive cases involved coinfections with TiLV, bacteria, and ectoparasites. Megalocytes with basophilic intracytoplasmic inclusion bodies were detected along with hemosiderin deposits in the anterior kidneys and spleens of the ISKNV‐positive fish. ISKNV was confirmed by PCR and in situ hybridization. The virus was successfully isolated in red hybrid tilapia brain (RHTiB) cells, showing cytopathic effects within 2–5 days postinfection. Phylogenetic analysis of the major capsid protein gene clustered the Thai isolate within ISKNV Clade 1, related to other Asian strains. Our findings highlight the need to include ISKNV in routine diagnostic surveillance and the importance of implementing integrated health management strategies focused on the early life stages of fish in intensive tilapia production systems.

Isolation and In Vitro Characterization of Two Lytic Jumbo Bacteriophages Targeting Aeromonas dhakensis for Biocontrol in Aquaculture - Tharindu Polwatta Gallage; Phongsawat Paisantham; Thitima Srathongneam; Heera Rajandas; Sivachandran Parimannan; Eakapol Wangkahart; Win Surachetpong; Rojana Sukchawalit; Skorn Mongkolsuk; Kwanrawee Sirikanchana (Journal of Fish Diseases, 2026)
Motile Aeromonas septicemia is a major bacterial disease in aquaculture, and the role of Aeromonas dhakensis has likely been underestimated due to frequent misidentification. Alternative control strategies for this pathogen remain limited. In this study, two lytic jumbo bacteriophages, DJC6219 and NK62157, were isolated from municipal wastewater and characterized for their potential as candidate biocontrol agents against A. dhakensis . Both phages were evaluated using host range assays, transmission electron microscopy, stability tests, multiplicity of infection (MOI) optimization, growth kinetics, and genomic analyses. Both phages showed high specificity toward A. dhakensis . They had icosahedral heads and long non‐contractile tails, consistent with siphovirus‐like phages. Both phages remained stable within moderate temperature and pH ranges but showed reduced viability under extreme conditions. Growth inhibition was observed at MOIs of 0.1–1, while a phage cocktail achieved enhanced bacterial suppression at an MOI of 0.01. Genomic analysis confirmed that both phages are lytic and carried no antimicrobial resistance genes, virulence factors, or lysogeny‐related genes. Comparative analysis indicated that both phages are closely related to known Aeromonas phages while representing independent environmental isolates. Our findings highlight the potential of DJC6219 and NK62157 as candidate biocontrol agents against A. dhakensis in aquaculture.

Temperature‐Driven Changes in Mortality and Environmental Shedding of TiLV in Nile Tilapia - Jidapa Yamkasem; Montakarn Sresung; Supitchaya Theplhar; Kwanrawee Sirikanchana; Skorn Mongkolsuk; Win Surachetpong; Tuchakorn Lertwanakarn (Journal of Fish Diseases, 2026)
Water temperature is a critical environmental factor influencing the severity, replication and transmission of infectious diseases in aquaculture. However, its role in the pathogenesis and shedding dynamics of tilapia lake virus (TiLV), which is an emerging viral pathogen threatening global tilapia production, remains to be fully characterised. We therefore evaluated the temperature‐dependent effects of TiLV infection in Nile tilapia ( Oreochromis niloticus ) by simulating direct and indirect cohabitation models. The fish were challenged with TiLV and maintained at 24°C, 28°C or 32°C. The highest mortality and viral loads in water and mucus occurred at 28°C, while outcomes at 32°C showed lower mortality, indicating a non‐monotonic temperature response. In contrast, infection at 24°C resulted in delayed infection onset, lower viral shedding and minimal mortality among the cohabitant fish. Notably, the indirect cohabitation system consistently showed reduced transmission and lower mortality among the cohabitant fish. The TiLV concentrations in the water and mucus peaked prior to the highest mortality events in both cohabitation experiments, which supports their applicability as noninvasive early warning indicators before outbreaks occur. Our findings demonstrate that tilapia mortality and shedding dynamics of TiLV are significantly influenced by fixed water temperature. These results provide a baseline for understanding how fixed thermal regimes impact TiLV outbreaks and highlight the importance of environmental monitoring in control strategies.

Emerging Viruses in Decapod Crustaceans: A Global Review - Xuan Dong; Guohao Wang; Kejun Wang; Kaisong Zhang; Hua Xu; Liying Wang; Xuan Li; Liang Qiu; Win Surachetpong; Jing Wang; Jee Eun Han; Kathy F. J. Tang; et al. (Reviews in Aquaculture, 2026)
Due to its advantages of a short production cycle, wide market demand, and profitability, decapod crustacean aquaculture has become one of the fastest‐growing food production systems. However, disease outbreaks have become one of the most important factors limiting the sustainability of decapod crustaceans. This review synthesizes current advancements in the understanding of emerging viral pathogens in decapod crustacean aquaculture, with emphasis on their genomic‐based taxonomical classification, susceptible hosts, global distribution, clinical manifestations, pathogenic mechanisms, diagnostic developments, and management strategies. This paper summarizes details of emerging viruses with confirmed pathogenicity (such as decapod iridescent virus 1), as well as viruses with uncertain or yet‐unconfirmed pathogenic roles. In addition, we highlight the role of next‐generation sequencing in virus discovery and examine the challenges posed by coinfection with other microorganisms. This review provides information to help the decapod crustacean aquaculture industry in setting up early warning systems to prevent the introduction of emerging pathogens into the production systems.

Tracing a Decade of Tilapia Lake Virus Research: Breakthroughs, Challenges, and Projections - Dorothea V. Megarani; Christopher J. Martyniuk; Roy P. E. Yanong; Felipe Pierezan; Win Surachetpong; Kuttichantran Subramaniam (Reviews in Aquaculture, 2026)
Tilapia are one of the most farmed fish groups worldwide, with global production exceeding 6.55 million tons in 2022, generating an estimated market value of approximately USD 20.9 billion. Tilapia are favored for their fast growth rate, adaptability to various farming environments, and high nutritional value as a protein source. However, the tilapia industry has encountered a significant challenge with the emergence of tilapia lake virus (TiLV), first noted in 2014. This highly contagious virus has the potential to devastate tilapia populations, leading to substantial economic losses and raising serious concerns about food security in countries reliant on this fish for livelihoods and sustenance. The rapid spread of TiLV and its significant impact on the tilapia industry have led to widespread concerns among stakeholders, researchers, and policymakers. In response, there has been an increasing focus on research and development of effective strategies to control and manage TiLV infections. This review paper aims to provide a comprehensive overview of the substantial advancements in the understanding of TiLV, delving into its genetic variation and manipulation, molecular pathogenesis, epidemiology, transmission pathways, clinical signs, diagnosis, and the underlying pathogenesis of the virus. Additionally, we summarize the current knowledge on the potential impact of TiLV on the global tilapia industry and the measures being implemented to control its spread. Finally, we discuss ongoing scientific efforts toward the development of vaccines and other innovative strategies for effectively managing TiLV infections, highlighting the importance of continued research to secure the future of tilapia aquaculture on a global scale.

One‐Pot RT ‐ LAMP CRISPR /Cas12b Platform for Rapid Detection of Tilapia Lake Virus - Dorothea V. Megarani; Lilia Yang; Hannah J. Siler; Eva M. Quijano Cardé; Christopher J. Martyniuk; Paul M. Hick; Joy A. Becker; Esteban Soto; Win Surachetpong; Roy P. E. Yanong; Kuttichantran Subramaniam (Journal of Fish Diseases, 2026)
Tilapia Lake Virus (TiLV) is a significant threat to global tilapia aquaculture, highlighting the need for rapid and accurate diagnostic methods to manage outbreaks and minimise economic losses. This study presents the development and partial validation of a one‐pot assay integrating RT‐LAMP with the CRISPR/Cas12b system for sensitive and specific TiLV detection. This assay amplifies viral RNA using RT‐LAMP, while CRISPR/Cas12b enables a real‐time detectable signal. Targeting a conserved region in TiLV segment four, the assay achieves results within 75 min at 62°C, with easy visualisation using a portable fluorescence viewer. It demonstrated high sensitivity, with a 95% limit of detection of 79.6 copies (95% CI: 48–132 copies), and high specificity, with no cross‐reaction to other fish RNA or DNA viruses. Based on a validation panel of 261 samples from 9 source populations, the assay exhibited 92% diagnostic sensitivity (95% CI: 87%–96%) and 100% diagnostic specificity (95% CI: 97%–100%). When assessed as a non‐lethal sample, gills provided a reliable and less invasive alternative despite lower viral loads compared to internal organs. Therefore, this partially validated one‐pot assay is potentially practical for enhancing TiLV detection and disease management in aquaculture systems, especially in field settings and resource‐limited laboratories.

The role of the circadian clock gene cry1 in the regulation of the antiviral response in zebrafish (Danio rerio) larvae - Mikolaj Mazur; Niedharsan Pooranachandran; Maria Zawisza; Zaneta Baran; Anna Michalik; Mikolaj Adamek; Magdalena Marcinkowska; Win Surachetpong; Tomasz K. Prajsnar; Krzysztof Rakus; Lukasz Pijanowski; Magdalena Chadzinska (Fish & Shellfish Immunology, 2026)

The role of cholesterol 25-hydroxylase in viral infections in zebrafish - Justyna Starzyk; Artem Voitsekhovskyi; Maria Zawisza; Niedharsan Pooranachandran; Alberto Falco; Win Surachetpong; Magdalena Chadzinska; Mikołaj Adamek; Krzysztof Rakus (Fish & Shellfish Immunology, 2025)

Granulocyte tropism and lymphocyte depletion highlight the immunopathogenesis of tilapia lake virus infection in Nile tilapia - Natthakul Youngnoi; Jidapa Yamkasem; Matepiya Khemthong; Piyathip Setthawong; Teerawut Nedumpun; Win Surachetpong; Tuchakorn Lertwanakarn (Fish & Shellfish Immunology, 2025)

Development and Efficacy of a Chitosan Nanoparticle‐Based Immersion Vaccine Targeting Segment 4 of Tilapia Lake Virus - Chanasorn Thanapasuk; Puntanat Tattiyapong; Jidapa Yamkasem; Sirikorn Kitiyodom; Piyathip Setthawong; Tuchakorn Lertwanakarn; Win Surachetpong (Journal of Fish Diseases, 2025)
Tilapia lake virus disease (TiLVD), which is caused by tilapia lake virus (TiLV), has resulted in significant damage to global tilapia farming. TiLV is a negative‐sense single‐strand RNA virus consisting of 10 genome segments. To date, no commercial vaccine against TiLVD has been developed, and effective strategies to control and prevent TiLVD are lacking. In this study, we developed and tested a chitosan nanoparticle‐based immersion recombinant protein targeting segment 4 (S4) of TiLV under both laboratory and field conditions. The open reading frame of S4 of TiLV was cloned into pET28a (+) and expressed by Escherichia coli BL21(DE3). The size of the nanoTiLV‐S4 (CNS4) vaccine was 284 ± 9.2 nm, which is smaller than the pre‐nanoencapsulation vaccine size of 2268 ± 41.8 nm. Transmission electron microscopy revealed that the nanoS4 particles had a round shape, uniform appearance and positive zeta potential of 17.7 ± 0.7 mV. Further analysis showed that the nanoS4 antigen was deposited on the fish gills and intestines and taken up into the epithelial cells within 30 min of immersion. Under laboratory infection using a cohabitation challenge model, the CNS4 vaccine demonstrated a relative percent survival (RPS) of 25%. In field conditions, the vaccine showed an RPS of 31.88% compared to the unvaccinated group. Overall, our study demonstrates that the new nanoTiLV‐S4 vaccine can be absorbed by the fish epithelium and reduces mortality caused by TiLV. However, further optimisation and field trials are necessary to improve the efficacy of the CNS4 vaccine and to test it under various farm conditions.

Beating Cardiac Cell Cultures From Different Developmental Stages of Rainbow Trout as a Novel Approach for Replication of Cardiac Fish Viruses - Torben Krebs; Julia Bauer; Sarah Graff; Lukas Teich; Markus Sterneberg; Marina Gebert; Henrike Seibel; Bettina Seeger; John Hellmann; Øystein Wessel; Espen Rimstad; Win Surachetpong; et al. (Journal of Fish Diseases, 2025)
Piscine orthoreovirus‐1 and 3 (PRV‐1, PRV‐3) cause highly prevalent infection in cultured salmonids and can induce heart and skeletal muscle inflammation (HSMI) resulting in economic losses in aquaculture. However, to date, PRV‐1 and PRV‐3 have withstood replication in continuous cell lines. In this study, we used beating heart cell cultures obtained from different developmental stages of rainbow trout ( Oncorhynchus mykiss ) (RTC‐L and RTC‐A) and tested their ability to sustain replication of PRV‐1 and PRV‐3. Furthermore, we compared the replication pattern of the different viruses with those in the newly developed heart fibroblast cell line (RTH‐F) and the traditional established rainbow trout gonad cell line (RTG‐2). Neither RTCs nor RTH‐F cell lines supported replication of PRV‐1 and PRV‐3. Comparative experiments showed varying susceptibility of the novel cultures to viral haemorrhagic septicaemia virus (VHSV), chum salmon reovirus (CSV), infectious pancreatic necrosis virus (IPNV), piscine myocarditis virus (PMCV), salmonid alphavirus 3 (SAV‐3) and tilapia lake virus (TiLV), indicating their usability for work with multiple fish viruses. While confirming the difficulty of replicating PRV‐1 and PRV‐3, the results demonstrate the potential of novel heart‐derived cell cultures as in vitro tools for studying fish viruses.

Diagnosis, isolation and description of a novel amnoonvirus recovered from diseased fancy guppies, Poecilia reticulata - Esteban Soto; Benjamin R. LaFrentz; Susan Yun; Dorothea Megarani; Eileen Henderson; Chutchai Piewbang; Amber E. Johnston; Somporn Techangamsuwan; Terry Fei Fan Ng; Janet Warg; Win Surachetpong; Kuttichantran Subramaniam (Journal of Fish Diseases, 2024)
The guppy, Poecilia reticulata , is one of the most common cultured ornamental fish species, and a popular pet fish highly desired by hobbyists worldwide due to its availability of many brilliantly coloured fish of many varieties. The susceptibility of guppies to diseases presents a remarkable concern for both breeders and hobbyists. In this study, we report the emergence of disease in fancy guppies caused by a previously uncharacterized virus in the USA. This virus was isolated from moribund guppies in two separate outbreaks in California and Alabama, from December 2021 to June 2023. The infected guppies presented with acute morbidity and mortality shortly after shipping, displaying nonspecific clinical signs and gross changes including lethargy, anorexia, swimming at the water surface, gill pallor, mild to moderate coelomic distension and occasional skin lesions including protruding scales, skin ulcers and hyperaemia. Histological changes in affected fish were mild and nonspecific; however, liver and testes from moribund fish were positive for Tilapia lake virus (TiLV), the single described member in the family Amnoonviridae , using immunohistochemistry and in situ hybridization, although the latter was weak. A virus was successfully recovered following tissue inoculation on epithelioma papulosum cyprini and snakehead fish cell lines. Whole genome sequencing and phylogenetic analyses revealed nucleotide and amino acid homologies from 78.3%–91.2%, and 78.2%–97.7%, respectively, when comparing the guppy virus genomes to TiLV isolates. Based on the criteria outlined herein, we propose the classification of this new virus, fancy tailed guppy virus (FTGV), as a member of the family Amnoonviridae , with the name Tilapinevirus poikilos (from the Greek ‘poikilos’, meaning of many colours; various sorts, akin to ‘poecilia’).

Tilapia lake virus infection disrupts the gut microbiota of red hybrid tilapia (Oreochromis spp.) - Suwimon Paimeeka; Chontida Tangsongcharoen; Tuchakorn Lertwanakarn; Piyathip Setthawong; Apinya Bunkhean; Marut Tangwattanachuleeporn; Win Surachetpong (Aquaculture, 2024)

First report of natural Cyprinid herpesvirus-2 infection associated with fatal outbreaks of goldfish (Carassius auratus) farms in Thailand - Chutchai Piewbang; Sabrina Wahyu Wardhani; Sirintra Sirivisoot; Win Surachetpong; Wanna Sirimanapong; Tanit Kasantikul; Somporn Techangamsuwan (Aquaculture, 2024)

Effects of light and circadian clock on the antiviral immune response in zebrafish - Mikolaj Mazur; Krzysztof Rakus; Mikolaj Adamek; Win Surachetpong; Magdalena Chadzinska; Lukasz Pijanowski (Fish & Shellfish Immunology, 2023)

A specific and sensitive droplet digital polymerase chain reaction assay for the detection of tilapia lake virus in fish tissue and environmental samples - Neetu Shahi; Tharinthon Prasartset; Win Surachetpong (Journal of Fish Diseases, 2023)
Tilapia lake virus (TiLV) causes high mortality in farmed and wild tilapia in various countries. We developed a highly specific and sensitive droplet digital polymerase chain reaction (ddPCR) assay to detect and quantify TiLV. The ddPCR assay could detect the virus at a lower threshold than the reverse transcription‐quantitative polymerase reaction (RT‐qPCR) method, and the sensitivity of the ddPCR assay was 10‐fold higher. The diagnostic sensitivity and specificity of the ddPCR assay were 100% and did not cross‐react with tilapia tissues infected with Tilapia parvovirus, Infectious spleen and kidney necrosis virus, Aeromonas hydrophila , Streptococcus agalactiae , S. iniae and Francisella noatunensis . The assay reproducibility was demonstrated by a high correlation coefficient of 0.998, and the inter‐assay coefficients of variability indicated that the ddPCR assay exhibited low variability within and between measurements. The detection limit of the TiLV ddPCR assay was 100 fg cDNA, which is equal to 3.3 copies of TiLV. Furthermore, the ddPCR assay could detect TiLV in mucus, water and infected tissue samples and the lowest copy number of TiLV detected in water samples by the ddPCR assay was 7.9 ± 0.99 copies/reaction The results of the clinical samples tested for TiLV revealed that the ddPCR assay had a relatively higher detection rate than the RT‐qPCR method. Overall, the ddPCR method offers a highly promising approach for the absolute quantification of TiLV in carrier fish and samples from the environment with low viral concentrations.

Review of alternatives to antibiotic use in aquaculture - Melba G. Bondad‐Reantaso; Brett MacKinnon; Iddya Karunasagar; Sophie Fridman; Victoria Alday‐Sanz; Edgar Brun; Marc Le Groumellec; Aihua Li; Win Surachetpong; Indrani Karunasagar; Bin Hao; Andrea Dall'Occo; et al. (Reviews in Aquaculture, 2023)
With the rapid growth of the aquaculture production since the 1980s, there has been a concomitant increase in disease outbreaks. The injudicious and/or incorrect use of antimicrobial agents against diseases of farmed aquatic species poses a considerable threat to the development and growth of a successful and sustainable aquaculture industry. An increase in antimicrobial resistance (AMR) is an important consequence, resulting to the difficulty in treating common bacterial diseases in populations of aquatic organisms, combined with the presence of antibiotic residues in food fish and their products, leading to import refusals and negative impacts on international trade. To reduce the frequency of AMR, good aquaculture and effective biosecurity practices should include the prudent and responsible use of antibiotics and also consider the use of alternatives to antibiotics, in addition to disease prevention management. This article reviews the literature discussing the scope of the problem pertaining to antibiotic use, the emergence of AMR in aquaculture and to consider and discuss viable alternatives (e.g., vaccination, bacteriophages, quorum quenching, probiotics and prebiotics, chicken egg yolk antibody and medicinal plant derivative). We also discuss lessons learnt, from specific case studies such as the vaccination of farmed salmon in Norway and the use of ‘specific pathogen‐free’ seed—as primary and essential part of a biosecurity strategy.

RNA-Seq Reveals Differential Gene Expression Patterns Related to Reproduction in the Golden Mahseer - Neetu Shahi; Bhupendra Singh; Sumanta Kumar Mallik; Debajit Sarma; Win Surachetpong (Fishes, 2023)
Golden mahseer (Tor putitora) is a critically endangered fish with significant economic importance. However, its reproductive challenges in a captive environment pose a limitation to the successful domestication and aquaculture potential of this species. To understand the role of various genes in gonad maturation and reproduction in golden mahseer, we conducted an RNA-sequencing (RNA-Seq) study on the brains of mature male and female specimens. Altogether, 20.6 and 21.5 million reads were generated from the brains of the male and female fish, respectively. A total of 26,989 and 55,600 cDNA coding sequences (CDS) were identified from the male and female brains, respectively, among which 26,258 CDS from the male brain and 53,446 CDS from the female brain demonstrated homology to known protein database sequences. A comprehensive analysis revealed a total of 1187 distinct differentially expressed upregulated genes (DEGs), encompassing 953 DEGs anticipated to exhibit upregulation in the female brain and 234 DEGs in the male brain. Furthermore, in the brain of female and male golden mahseer, a significant downregulation was observed in 492 and 744 genes, respectively, resulting in a cumulative count of 1236 downregulated genes. Validation of the RNA-Seq results was performed by quantitative real-time PCR (qPCR) using 24 genes. Sixteen candidate genes with differential expression levels between the male and female fish were then selected and analyzed via qPCR. The results confirmed that amh, foxl3, dax1, kif20, and tkt were upregulated in the male golden mahseer brain, while cyp19a1a, dmrt2a, gdf9, sox9b, wt-1a, and aqp1 were upregulated in the female golden mahseer brain. Our study elucidates the distinct gene expression profiles in male and female golden mahseer brains and thus offers valuable insights for potential reproductive manipulation strategies in this fish species.

How susceptible are rainbow trout and brown trout to infection with tilapia lake virus at increased water temperature – Is there any potential for climate change driven host jump? - Mikolaj Adamek; Marek Matras; Win Surachetpong; Krzysztof Rakus; Magdalena Stachnik; Julia Bauer; Alberto Falco; Verena Jung-Schroers; Chutchai Piewbang; Somporn Techangamsuwan; Sahar Abd El Rahman; Richard Paley; et al. (Aquaculture, 2023)

Concurrent infections of Streptococcus iniae and Aeromonas veronii in farmed Giant snakehead ( Channa micropeltes ) - Theeraporn Pulpipat; Taylor I. Heckman; Visanu Boonyawiwat; Pattarawit Kerddee; Sakuna Phatthanakunanan; Esteban Soto; Win Surachetpong (Journal of Fish Diseases, 2023)
The giant snakehead, Channa micropeltes , is an increasingly important economic freshwater fish in Thailand and other regions of Asia. Presently, giant snakehead are cultured under intensive aquaculture conditions, leading to high stress and conditions favouring disease. In this study, we reported a disease outbreak in farmed giant snakehead with a cumulative mortality of 52.5%, continuing for 2 months. The affected fish exhibited signs of lethargy, anorexia and haemorrhage of the skin and eyes. Further bacterial isolations revealed two different types of colonies on tryptic soy agar: small white, punctate colonies of gram‐positive cocci and cream‐coloured, round and convex colonies of rod‐shaped gram‐negative bacteria. Additional biochemical and species‐specific PCR analysis based on 16S rRNA confirmed the isolates as Streptococcus iniae and Aeromonas veronii . Multilocus sequence analysis (MLSA) placed the S . iniae isolate into a large clade of strains from clinically infected fish worldwide. Gross necropsy findings showed liver congestion, pericarditis and white nodules in the kidney and liver. Histologically, the affected fish showed focal to multifocal granulomas with inflammatory cell infiltration in kidney and liver, enlarged blood vessels with mild congestion within the meninges of the brain and severe necrotizing and suppurative pericarditis with myocardial infarction. Antibiotic susceptibility tests revealed that S . iniae was sensitive to amoxicillin, erythromycin, enrofloxacin, oxytetracycline, doxycycline and resistant to sulfamethoxazole‐trimethoprim, while the A . veronii was susceptible to erythromycin, enrofloxacin, oxytetracycline, doxycycline, sulfamethoxazole‐trimethoprim and resistant to amoxicillin. Conclusively, our findings highlighted the natural concurrent bacterial infections in cultured giant snakehead, which support the implementation of appropriate treatment and control strategies.

Tilapia lake virus ( TiLV ) causes severe anaemia and systemic disease in tilapia - Jessica Kaye Turner; Sasakorn Sakulpolwat; Suchanuch Sukdanon; Tuchakorn Lertwanakarn; Pitchaporn Waiyamitra; Chutchai Piewbang; Felipe Pierezan; Somporn Techangamsuwan; Esteban Soto; Win Surachetpong (Journal of Fish Diseases, 2023)
Tilapia lake virus disease (TiLVD) is an emerging disease in tilapia that is associated with mass mortality affecting global tilapia aquaculture. In this study, red hybrid tilapias ( Oreochromis spp.) were experimentally infected by intracoelomic injection with Tilapia lake virus (TiLV) to gain a better understanding of the clinicopathological changes during infection. Pale bodies and gill were observed in infected fish after 7 days of post‐challenge (dpc) associated with severe anaemia. Further haematological analysis in TiLV‐infected fish revealed decreased levels of haemoglobin and haematocrit at 3 dpc. Common pathological findings included pale and friable liver, pale intestine with catarrhal content, and dark and shrunken spleen in TiLV‐infected fish at 7 dpc and 14 dpc. Histologically, reduced numbers of red blood cells and accumulation of melano‐macrophage centre in the spleen were found in infected fish at 3 dpc, and severe lesions were more commonly observed at 7 and 14 dpc. Lymphocyte infiltration, syncytial cell formation and multifocal necrotic hepatitis were the prominent pathological findings in the liver of infected fish. The severity of pathological changes was associated with TiLV‐infection with higher viral loads and with the expression pattern of pro‐inflammatory cytokines and antiviral genes, including interferon regulatory factor 1 ( irf1) , interleukin ( il‐8 ), radical s‐adenosyl methionine domain containing 2 ( rsad2 ) and mx . Our study provides a comprehensive analysis of the haematological profile and pathological changes in tilapia during TiLV infection. Overall, lesions present in various organs, together with alteration of host immune response in TiLV‐infected fish, indicate the systemic infection of this virus. The knowledge gained from this study improves our understanding of how TiLV causes pathological and haematological changes in tilapia.

Simultaneous detection of three important viruses affecting tilapia using a multiplex PCR assay - Tharinthon Prasartset; Win Surachetpong (Journal of Fish Diseases, 2023)

Strategies to enhance tilapia immunity to improve their health in aquaculture - Bei Wang; Kim D. Thompson; Eakapol Wangkahart; Jidapa Yamkasem; Melba G. Bondad‐Reantaso; Puntanat Tattiyapong; Jichan Jian; Win Surachetpong (Reviews in Aquaculture, 2023)
Various emerging and re‐emerging diseases, such as streptococcosis, tilapia lake virus disease and infectious spleen and kidney necrosis virus disease, have had a significant economic impact on the tilapia industry over the last decade. These diseases have resulted in high levels of morbidity and mortality, production losses and trade restrictions. In the absence of effective husbandry management, disease prevention strategies and appropriate biosecurity measures, infectious diseases will continue to challenge the sustainability of global tilapia aquaculture. Strategies used to reduce the impact of disease include feeding probiotic and prebiotic supplements to enhance tilapia health and to modulate the fish's gut microbiota to improve gut health. Herbal medicines and immunostimulants are also used to enhance immunity to disease, while vaccines are available, or are under development, for a number of economically important pathogens affecting tilapia culture. This review provides an overview of the benefits of enhancing the immune response of tilapia to improve their health, and in turn reduce the levels of pathogens within tilapia farming systems.

Specific and rapid detection of tilapia parvovirus using loop‐mediated isothermal amplification ( LAMP ) method - Theerawut Phusantisampan; Jidapa Yamkasem; Puntanat Tattiyapong; Malinee Sriariyanun; Win Surachetpong (Journal of Fish Diseases, 2022)

Assessing the effect of probiotics on tilapia lake virus‐infected tilapia: Transmission and immune response - Ying‐Fei Yang; Jidapa Yamkasem; Win Surachetpong; Yi‐Jun Lin; Shu‐Han You; Tien‐Hsuan Lu; Chi‐Yun Chen; Wei‐Min Wang; Chung‐Min Liao (Journal of Fish Diseases, 2022)
Probiotics have been used to alleviate disease transmission in aquaculture. However, there are limited studies on probiotic use in modulating tilapia lake virus (TiLV). We assessed commercially available probiotic supplements used in TiLV‐infected tilapia and performed mortality and cohabitation assays. We developed a mechanistic approach to predict dose–response interactions of probiotic effects on mortality and immune gene response. We used a susceptible–infected–mortality disease model to assess key epidemiological parameters such as transmission rate and basic reproduction number ( R 0 ) based on our viral load dynamic data. We found that the most marked benefits of probiotics are significantly associated with immune system enhancements (~30%) and reductions in disease transmission (~80%) and R 0 (~70%) in tilapia populations, resulting in a higher tolerance of farming densities (~400 fold) in aquaculture. These findings provide early insights as to how probiotic use‐related factors may influence TiLV transmission and the immune responses in TiLV‐infected tilapia. Our study facilitates understanding the mode of action of probiotics in disease containment and predicting better probiotic dosages in diet and supplements to achieve the optimal culturing conditions. Overall, our analysis assures that further study of rationally designed and targeted probiotics, or mechanistic modelling is warranted on the basis of promising early data of this approach.

Persistence of Tilapia tilapinevirus in fish rearing and environmental water and its ability to infect cell line - Jidapa Yamkasem; Tharinthon Prasartset; Puntanat Tattiyapong; Kwanrawee Sirikanchana; Skorn Mongkolsuk; Esteban Soto; Win Surachetpong (Journal of Fish Diseases, 2022)
Tilapia tilapinevirus , or Tilapia Lake Virus (TiLV), is a RNA virus associated with mass morbidity and mortality in tilapia, leading to severe economic losses for global tilapia aquaculture. In this study, we investigated the persistence of TiLV in water by spiking sterile distilled water (SDW), freshwater collected from rearing fish tanks (FW) and natural pond water (PW) at 27°C as a representative of environmental water conditions with 0.6 ml of stock virus (3.18 × 10 7 viral copies/ml of water). The water samples were filtered through an electronegative charge membrane and quantified using reverse transcriptase quantitative PCR at 0, 3, 5, 7, 10 and 14 days post‐inoculation. The results revealed that TiLV RNA in SDW was reduced by 1.34 log 10 in 14 days. A similar approximately 4 log 10 removal of the virus in FW and PW was observed at 3 and 7 days, respectively. Moreover, the infectivity of TiLV was further studied; the virus lost its infectivity in E‐11 cells after 1 day in SDW, FW and PW water samples, even though the virus was spiked 10 more times than in the viral persistence study. Taken together, the results could be applied to improving biosecurity practices in tilapia farms by disinfecting or resting reservoir water for at least three to five days prior to stocking tilapia, to limit the spread of TiLV.

Development and application of TaqMan probe‐based quantitative PCR assays for the detection of tilapia parvovirus - Jidapa Yamkasem; Puntanat Tattiyapong; Win Surachetpong (Journal of Fish Diseases, 2022)
Tilapia parvovirus (TiPV) is a novel parvovirus associated with high mortality in Nile tilapia and red hybrid tilapia, leading to severe economic losses for tilapia aquaculture. It is critical to develop a sensitive and accurate assay to detect TiPV in fish tissues. In this study, new TaqMan probe‐based quantitative PCR (qPCR) assays targeting the non‐structural (NS) and viral protein (VP) genes of TiPV were developed. The standard curves of the assays were 95.64%–98.96% over a wide linear range of 10 9 –10 1 copies of the corresponding standard DNA per reaction. The intra‐ and inter‐assay coefficients of variation were in the ranges 0.54%–2.50% and 0.13%–1.17%, respectively, which suggests good repeatability and reproducibility. The detection limit of the TaqMan TiPV assays was 10 copies/µl. The application of the TaqMan qPCR assays to field samples revealed that they had comparable sensitivity to a previously developed SYBR Green qPCR, but more sensitive than the conventional PCR. No cross‐reactivity of the TaqMan TiPV assays was found with the samples infected with other viruses and bacteria. Overall, the assays offered high sensitivity and specificity in the detection of low concentrations of TiPV DNA in infected tilapia samples. These new TaqMan qPCR assays could provide a valuable diagnostic tool for the reliable and specific detection of TiPV in experimental and field samples.

Tilapia lake virus: The story so far - Win Surachetpong; Sri Rajiv Kumar Roy; Pamela Nicholson (Journal of Fish Diseases, 2020)
Tilapia lake virus (TiLV) is a highly contagious pathogen that has detrimental effects on tilapia farming. This virus was discovered in 2014 and has received tremendous global attention from the aquaculture sector due to its association with high fish mortalities and its strong economic impact on the tilapia aquaculture industry. Currently, TiLV has been reported in 16 countries, and this number is continuing to rise due to improved diagnostic assays and surveillance activities around the world. In this review, we summarize the up‐to‐date knowledge of TiLV with regard to TiLV host species, the clinical signs of a TiLV infection, the affected tissues, pathogenesis and potential disease risk factors. We also describe the reported information concerning the virus itself: its morphology, genetic make‐up and transmission pathways. We review the current methods for virus detection and potential control measures. We close the review of the TiLV story so far, by offering a commentary on the major TiLV research gaps, why these are delaying future TiLV research and why the TiLV field needs to come together and proceed as a more collaborative scientific community if there is any hope limiting the impact of this serious virus.

Virucidal effects of common disinfectants against tilapia lake virus - Phitchaya Jaemwimol; Kwanrawee Sirikanchana; Puntanat Tattiyapong; Skorn Mongkolsuk; Win Surachetpong (Journal of Fish Diseases, 2019)
Tilapia lake virus (TiLV) is an emerging virus associated with high fish mortality and economic losses. This study investigates the virucidal effects of the following disinfectants (active ingredients) on TiLV: 2.5 ppm iodine, 10 ppm sodium hypochlorite (NaOCl), 300 ppm hydrogen peroxide (H 2 O 2 ), 80 ppm formalin and 5,000 ppm (0.5%) Virkon ® . Factors that affect the disinfectants’ efficacy, including temperature, contact time and soiling (organic matter) interference, were examined under conditions mimicking natural aquaculture practices. TiLV inactivation of higher than 5 log 10 TCID 50 ml −1 was achieved after 10 min and at 28°C for all disinfectants except formalin; similar inactivation levels were reached by NaOCl and Virkon ® at 10 min and 4°C. Extended exposure to formalin from 10 to 60 min at 28°C rendered more than 5 log 10 inactivation. Increasing synthetic organic matter in the water to mimic soiling interference reduced the efficacy of NaOCl, iodine and H 2 O 2 when tested at 10 min and 28°C; however, Virkon ® still achieved more than 5 log 10 inactivation. This study demonstrates that most common disinfectants effectively reduced viral loads to minimum levels. To limit the spread of TiLV in aquaculture farms and related facilities, the appropriate use of such disinfectants should therefore be promoted and implemented.

Evidence of potential vertical transmission of tilapia lake virus - Jidapa Yamkasem; Puntanat Tattiyapong; Attapon Kamlangdee; Win Surachetpong (Journal of Fish Diseases, 2019)
Tilapia lake virus disease (TiLVD) is an emerging viral disease in tilapia with worldwide distribution. Although the horizontal transmission of TiLV has been demonstrated through the cohabitation of infected fish with susceptible fish, no direct experiment showed the potential of vertical transmission from broodstock to progeny. In this study, natural outbreaks of TiLV in broodstock and fry in two tilapia hatcheries were confirmed. The TiLV genomic RNA was detected in liver and reproductive organs of infected broodstock, while infective virus was isolated in susceptible cell line. In situ hybridization assay confirmed the presence of TiLV in the ovary and testis of naturally infected fish and experimentally challenged fish. Moreover, early detection of TiLV in 2‐day‐old fry and the presence of TiLV genomic RNA and viable virus in the testis and ovary suggested the possible transfer of this virus from infected broodstock to progenies. As infective virus was present in gonads and fry in natural outbreak and experimental fish, the importance of biosecurity and prevention of the virus to establish in the hatchery should be emphasized. Hence, the development of TiLV‐free broodstock and the maintenance of high biosecurity standards in the hatcheries are essential for any attempt of virus eradication.

Intragastric and intracoelomic injection challenge models of tilapia lake virus infection in Nile tilapia ( Oreochromis niloticus L.) fingerlings - Felipe Pierezan; Susan Yun; Win Surachetpong; Esteban Soto (Journal of Fish Diseases, 2019)
To gain a better understanding of the pathogenesis of tilapia lake virus (TiLV) infections in Nile tilapia ( Oreochromis niloticus ), fingerlings were challenged with a single dose of 1 × 10 4 TCID 50 /fish of TiLV utilizing intracoelomic/intraperitoneal (IC ch ) or intragastric (IG ch ) routes. Acute mortalities were present in both groups, reaching 70 and 40% in IC ch and IG ch after 10 days, respectively. Challenged fish presented erratic swimming, lethargy, anorexia, exophthalmia and cutaneous petechiae and ecchymoses. Histological changes in challenged groups included syncytial formation, intracytoplasmic inclusion bodies and multifocal hepatocellular degeneration and necrosis. In addition, multifocal areas of mild proliferation of glial cells and lymphocytic perivascular cuffing were observed in the brain of exposed challenged groups. TiLV RNA was detected in gills and faeces of challenged fish using quantitative reverse transcriptase–PCR, as well as in the tank water holding challenged fish. Moreover, TiLV RNA was detected in scrolls obtained from formalin‐fixed paraffin‐embedded tissue blocks from challenged fish. Results from this study suggest that IG methods represent an additional method to study the pathogenesis of the disease in this species, as it results in infection and diseases as in naturally occurring cases and does not bypass important mucosal immune responses as injectable routes do.

Minimal risk of tilapia lake virus transmission via frozen tilapia fillets - Worrayanee Thammatorn; Pattarasuda Rawiwan; Win Surachetpong (Journal of Fish Diseases, 2019)
Recent outbreaks of a novel tilapia lake virus (TiLV) have raised concerns regarding the international spread of TiLV in frozen tilapia products. This study investigated the potential risks of frozen tilapia fillet as a source of TiLV transmission. It revealed that TiLV genomic RNA could be detected in tilapia fillet and the virus isolated from non‐frozen and frozen fillets with clinical TiLV infection stored up to 28 days caused a cytopathic effect (CPE) formation in the susceptible cell line in vitro. However, frozen fillets from clinical TiLV infection stored for 90 and 120 days did not cause CPE in the susceptible cell line. Similarly, CPE was not observed in TiLV isolated from subclinically TiLV‐infected fish fillets. In addition, in vivo bioassay revealed that despite the presence of TiLV isolated from subclinically TiLV‐infected fillet stored at −20°C for 14 days, there was no evidence of TiLV disease in naïve red hybrid tilapia based on the absence of clinical signs and mortality and without the detection of TiLV genomic RNA using reverse transcription–quantitative polymerase chain reaction assay. Collectively, these findings suggested minimal risk of transmission of TiLV via frozen tilapia fillets.